Effective Privacy Preserving in Networks Using Merkle Hash Trees - Sunitha, A; reddy, K Sudha (IJRDO -Journal of Computer Science Engineering, 2015)
The design of two-tiered sensing element networks, wherever storage nodes function Associate in performing intermediate tier between sensors and a sink for storing knowledge and process queries, has been wide adopted thanks to the advantages of power and storage saving for sensors yet because the potency of question process. However, the importance of storage nodes conjointly makes them enticing to attackers during this paper, we have a tendency to propose SafeQ, a protocol that forestalls attackers from gaining info from each sensing element collected knowledge and sink issued queries. SafeQ conjointly permits a sink to observe compromised storage nodes after they act. To preserve privacy, SafeQ uses a unique technique to cypher each knowledge and queries such a storage node will properly method encoded queries over encoded knowledge while not knowing their values. To preserve integrity, we have a tendency to propose 2 schemes—one victimization Merkle hash trees and another employing a new system referred to as neighborhood chains—to generate integrity verification info so a sink will use this info to verify whether or not the results of a question contains precisely the knowledge things that satisfy the query to boost performance, we have a tendency to propose Associate in Nursing optimization technique victimization Bloom filters to scale back the communication price between sensors and storage nodes